2019
DOI: 10.22259/2639-1783.0201007
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Academic Stress and Self-Control among Faculty of Nursing Students

Abstract: Background: Psychiatric/mental health nursing is one of the core courses for undergraduate nursing students, but the complex and abstract nature of much of the psychiatric mental health course content makes it a challenge for many students. The aim was to examine the relationship between academic stress and self-control among faculty of nursing students. Descriptive co-relational design was utilized to achieve the aim of the study. This study was carried out at Faculty of Nursing, Menoufia University. A conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…They cannot control themselves due to the stress they have. These findings are supportive Hashem(2019) that there is a very statistically significant relationship and a negative correlation between academic stress and self-control.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…They cannot control themselves due to the stress they have. These findings are supportive Hashem(2019) that there is a very statistically significant relationship and a negative correlation between academic stress and self-control.…”
Section: Discussionsupporting
confidence: 76%
“…For example, someone experiencing high levels of academic stress may forget important assignments, have difficulty concentrating, or tend to avoid challenging assignments. For example, in research conducted by Hashem (2019) the research subjects were 180 nursing students. This research has proven that there is a very statistically significant relationship and a negative correlation between academic stress and self-control among Nursing Faculty students.…”
Section: H4: Descriptive Norms Have a Significant Effect On Self-cont...mentioning
confidence: 99%
“…The study findings show differences from those of another research. Hashem et al (2019) found a negative relationship between academic stress and self-control in college students. In another study by Juhendra (2022), as a mediator variable, self-control is seen to perfectly mediate between academic stress and smartphone addiction.…”
Section: ) State Anxiety Directly and Indirectly Affectsmentioning
confidence: 90%